Product Development Projects Dynamics and Emergent Complexity - Schlick, Christopher; Demissie, Bruno; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book primarily explores two topics: the representation of simultaneous, cooperative work processes in product development projects with the help of statistical models, and the assessment of their emergent complexity using a metric from theoretical physics (Effective Measure Complexity, EMC). It is intended to promote more effective management of development projects by shifting the focus from the structural complexity of the product being developed to the dynamic complexity of the development processes involved. The book is divided into four main parts, the first of which provides an introduction to vector autoregression models, periodic vector autoregression models and linear dynamical systems for modeling cooperative work in product development projects. The second part presents theoretical approaches for assessing complexity in the product development environment, while the third highlights and explains closed-form solutions for the complexity metric EMC for vector autoregression models and linear dynamical systems. Lastly, part four validates the models and methods using a case study from the industry, together with several Monte Carlo experiments. Presenting a truly unique, integrated treatment of statistical approaches for modeling simultaneous, cooperative work processes in product development projects and assessing their complexity, the book offers a valuable resource for researchers in Industrial Engineering, Engineering Management and Project Management, as well as Project Managers seeking to model and evaluate their own development projects.
Introduction -- Mathematical Models of Cooperative Work in Product Development Projects -- Evaluation of Complexity in product development -- model-driven Evaluation of the Emergent Complexity of Cooperative Work based on Effective Measure Complexity -- Validity Analysis of Selected Closed-Form Solutions for Effective Measure Complexity -- Conclusions and Outlook.
Keywords: Dynamics; Nonlinear theories; Operations research; Management science; Engineering design; Industrial Management; Applied Dynamical Systems; Operations Research, Management Science; Engineering Design; Industrial Management